Impact of temperature on chlorination strategies for mussel control at water treatment plants - Carlos Alonzo-Moya (IWA Publishing, 2021)
Drinking water treatment plants in the Great Lakes often protect their intake structures against dreissenid biofouling by prechlorinating when water temperatures exceed 12 °C. This temperature threshold is based on the reproduction characteristics of zebra mussels. However, in recent years, zebra mussels have largely given way to quagga mussels in the region. These mussels reportedly reproduce at temperatures as low as 5 °C. The objective of this study was to determine if the current 12 °C trigger point for prechlorination remains appropriate. A 3-year monitoring program using bioboxes recorded mussel veliger concentrations and settlement potential in water drawn from the intakes of three drinking water treatment plants on Lake Ontario. Water temperature was a poor predictor of veliger presence and settlement. Reproduction and settlement were observed outside of the traditional temperature thresholds. Furthermore, no relationship was found between the number of veligers in the water column and those settling, suggesting that there are complex environmental factors that influence mussel activity. Nevertheless, it was observed that settlement occurred consistently between the months of July and November in the 3 years of the study. Therefore, a calendar-based approach to trigger prechlorination, as opposed to a temperature-based approach, is suggested. HIGHLIGHTS Settlement was observed at temperatures <5°C.; Temperature is a poor predictor of mussel veliger densities and settlement rates.; Settlement consistently occurred between the months of July and November.;